From past critiques to present challenges: A review of LCA approaches and results in the aluminum industry - Rossi, Federico; De Bernardi, Chiara; Frey, Marco; Niero, Monia (Waste management (Elmsford), 2025)
•Most updated literature review regarding application of LCA to aluminium production.•Literature adopts mass functional units, cradle-to-gate and substitution approaches.•LCA studies on new aluminium decarbonization and circular technologies are missing.•The use of PEF to aluminium production is scarcely explored in the literature. Aluminum is a critical raw material and a key resource in manufacturing. Hence, to promote environmental sustainability in this industry, Life Cycle Assessment has largely been used as a quantitative methodology for assessing its overall impact. However, since 2012, several advancements have been made to Life Cycle Assessment methodology in terms of the technologies considered and the waste management strategies used. This study, therefore, has two main aims: i) to assess whether the literature gaps identified in the last major review of Life Cycle Assessment in the aluminum sector, conducted in 2012, have now been addressed; and ii) to identify any new challenges in this sector for Life Cycle Assessment practitioners that might have emerged over the past 15 years. The results of this review show that there has been some convergence in methodological practices, particularly in terms of the definitions for functional units, system boundaries, and end-of-life modeling. However, there is also a huge margin for improvement. The environmental metrics used are typically not comparable. The main challenges remain when attempting to apply the Product Environmental Footprint method, and, further, exploring new decarbonization technologies and circular waste management strategies remains persistently difficult.